2007
DOI: 10.1111/j.1741-3737.2007.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Beliefs About Nonresident Fathers’ Obligations and Rights

Abstract: We examine whether parents rely on principles of equity or equality in making judgments about nonresident fathers’ obligations and rights. The data are taken from the first wave of the Fragile Families and Child Wellbeing Study. The analysis sample includes 4,304 new mothers and 3,414 new fathers. Results indicate that fathers perceive obligations and rights as independent concerns (equality principle), whereas mothers see obligations and rights as linked (equity principle). The findings raise questions about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
2
25
3
Order By: Relevance
“…Contrary to past findings that mothers believe fathers' visitation rights should depend on payment of child support (Lin & McLanahan, 2007), child support did not appear to motivate the mothers in this study to gatekeep nonresident fathers. The difference may be due to geographic isolation and social class.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to past findings that mothers believe fathers' visitation rights should depend on payment of child support (Lin & McLanahan, 2007), child support did not appear to motivate the mothers in this study to gatekeep nonresident fathers. The difference may be due to geographic isolation and social class.…”
Section: Discussioncontrasting
confidence: 99%
“…Perhaps the most commonly cited reason is the economic condition of the father (Huang & Pouncy, 2005;Lin & McLanahan, 2007;Sano et al, 2008). In their analysis of Current Population Survey data, Huang and Pouncy (2005) found that 21% of women without a child support order indicated objective constraints, such as a father being unable to pay or already paying what he can, as the main reason for not pursuing an order.…”
Section: Entering the Child Support Systemmentioning
confidence: 96%
“…Understanding how parents view their child support obligations is complex (Lin & McLanahan, 2007;Roy, 1999), and many custodial parents fail to receive their awarded child support (Grall, 2011). Receipt of payments is not straightforward and often involves negotiations between mothers, fathers, and the state.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, others found that mothers avoided court proceedings because their relationship with the father had been negative (e.g., abusive)(dail and Thieman 1996;edin 1995;Harris 2015;Waller and Plotnick 2001).Finally, as in south africa, a lack of information about the system on the mother's part(edin 1995;Harris 2015) and the inability of the father to pay were noted reasons for not pursuing a case(Harris 2015;Huang and Pouncy 2005;lin and Mclanahan 2007;sano, richards, and Zvonkovic 2008).…”
mentioning
confidence: 89%